Faktor-Faktor Yang Mempengaruhi Financial Performance Pada Perusahaan Manufaktur Di BEI - David Winarto, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence about the effects of financial leverage, firm size, andcorporate social responsibilityonfinancial performancein manufacturing industries listed in Indonesian Stock Exchange during the period of 2015-2017. This research used 64samples of manufacturing companies that have been previously selected using purposive sampling method. Secondary data was used in the form of financial information from the financial statements and annual reports. This research data was processed using EViews 10.The result of this research shows that financial leverage and firm size have a significant effect on financial performance, while corporate social responsibility does not has a significant effect on financial performance.Suggestions for the next study is to add another independent variables to be able to strengthen the ability of independent variables in explaining the dependent variable, such as intellectual capital, company age, and liquidity